2012
DOI: 10.1016/j.aca.2012.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Submicron hard X-ray fluorescence imaging of synthetic elements

Abstract: Synchrotron-based X-ray fluorescence microscopy (SXFM) using hard X-rays focused into sub-micron spots is a powerful technique for elemental quantification and mapping, as well as microspectroscopic measurement such as μ-XANES (X-ray absorption near edge structure). We have used SXFM to image and simultaneously quantify the transuranic element plutonium at the L3 or L2 edge as well as lighter biologically essential elements in individual rat pheochromocytoma (PC12) cells after exposure to the long-lived pluton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Synchrotron-based X-ray fluorescence microscopy (XFM) has opened remarkable opportunities for quantitative study of trace elements, particularly metals, within whole cells and tissue sections (Wagner et al, 2005;Paunesku et al, 2006;Fahrni, 2007;Finney et al, 2007;Szczerbowska-Boruchowska, 2007;Ortega et al, 2009;Paunesku et al, 2009;Ralle & Lutsenko, 2009;Fittschen & Falkenberg, 2011;Bohic et al, 2012;Jensen et al, 2012;Vogt & Ralle, 2012). By using spatially coherent highly brilliant X-rays from a synchrotron and advanced X-ray optics, current XFM instruments at the Advanced Photon Source (APS) at Argonne National Laboratory routinely achieve sub-micrometer probe size and are capable of detecting trace elements with a sensitivity down to parts per million (p.p.m.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrotron-based X-ray fluorescence microscopy (XFM) has opened remarkable opportunities for quantitative study of trace elements, particularly metals, within whole cells and tissue sections (Wagner et al, 2005;Paunesku et al, 2006;Fahrni, 2007;Finney et al, 2007;Szczerbowska-Boruchowska, 2007;Ortega et al, 2009;Paunesku et al, 2009;Ralle & Lutsenko, 2009;Fittschen & Falkenberg, 2011;Bohic et al, 2012;Jensen et al, 2012;Vogt & Ralle, 2012). By using spatially coherent highly brilliant X-rays from a synchrotron and advanced X-ray optics, current XFM instruments at the Advanced Photon Source (APS) at Argonne National Laboratory routinely achieve sub-micrometer probe size and are capable of detecting trace elements with a sensitivity down to parts per million (p.p.m.)…”
Section: Introductionmentioning
confidence: 99%
“…in whole cells or tissue sections. In addition, chemical state information, such as the oxidation state of elements, can be elucidated using X-ray fluorescence spectroscopy and X-ray absorption nearedge structure (XANES) (Norman, 1986;Dyar et al, 1998;Ortega et al, 2009;Gorman-Lewis et al, 2011;Bohic et al, 2012;Jensen et al, 2012;Vogt & Ralle, 2012;Oakes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Synchrotron-based XRF microscopy using hard X-rays focused into sub-micrometre spots is a powerful technique for elemental quantication and mapping, as well as performing m-XANES. Jensen et al 55 reported results of studies to quantify the transuranic element Pu at the L-3 or L-2 edge and also Th and lighter biologically essential elements in individual rat pheochromocytoma (PC12) cells aer exposure to the long lived isotope 242 Pu. Elemental maps demonstrated that Pu localised principally in the cytoplasm of the cell avoiding the cell nucleus, which was marked by the highest concentrations of P and Zn in these experiments.…”
Section: Synchrotron and Large Scale Facilitiesmentioning
confidence: 99%
“…Most actinide studies were carried out with actinides in higher oxidation states, especially with uranium(VI) (Carrière et al, 2004(Carrière et al, , 2005aMilgram et al, 2008aMilgram et al, , 2007Milgram et al, , 2008bMirto et al, 1999a,b;Muller et al, 2006;Rouas et al, 2010), for which the relationship between its speciation and its cytotoxicity onto mammalian cells is comprehensively studied. A second, well studied actinide is plutonium(IV), whose uptake and binding was studied with various cell lines Fouillit et al, 2004;Gorman-Lewis et al, 2011;Jensen et al, 2012Jensen et al, , 2011Planas-Bohne and Duffield, 1988;Planas-Bohne et al, 1985Planas-Bohne and Rau, 1990;Schuler and Taylor, 1987). For trivalent actinides, the chemical analogs of lanthanides, no studies concerning their biological interactions are reported up to date.…”
Section: Introductionmentioning
confidence: 99%